2019
DOI: 10.24310/abm.v44i0.5750
|View full text |Cite
|
Sign up to set email alerts
|

Adiciones y correcciones a la flora bentónica marina del Atlántico ibérico norte

Abstract: Continuando con los estudios para la actualización del inventariado de la flora bentónica marina del Atlántico Ibérico.En este trabajo se incluye nueva información de distribución para 18 especies (3 Cyanobacteria, 9 Rhodophyta, 4 Ochrophyta, 2 Chlorophyta) de algas bentónicas marinas, recolectadas en el intermareal y submareal de 46 localidades del atlántico ibérico norte. Atendiendo a la distribución de las especies recolectadas, cabe destacar una nueva cita para Europa (Plocamium cf. ovicorne), 3 nuevas cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Subsequently, specimens from Brittany were grouped with the Pacific lineage based on the plastid and mitochondrial DNA analyses by Zuccarello et al [2]. Populations of this species were also found in Belgium [15], the Netherlands [16], the Southern coast of England [17], in Aquitaine (France) [18], in Normandy (France) [19] and in Galicia (North-Western Spain) [20]. In the Mediterranean, C. okamurae was reported from two French localities: in Marseille in 2004 and later in Toulon [21].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, specimens from Brittany were grouped with the Pacific lineage based on the plastid and mitochondrial DNA analyses by Zuccarello et al [2]. Populations of this species were also found in Belgium [15], the Netherlands [16], the Southern coast of England [17], in Aquitaine (France) [18], in Normandy (France) [19] and in Galicia (North-Western Spain) [20]. In the Mediterranean, C. okamurae was reported from two French localities: in Marseille in 2004 and later in Toulon [21].…”
Section: Introductionmentioning
confidence: 99%
“…Dictyota cyanoloma was described in 2010, based on specimens from Palamós, NW Mediterranean [56], although the species was first reported from the Iberian Peninsula as D. ciliolata by Rull Lluch et al [57]. The species is widely distributed in the Mediterranean Sea and recent records have proven its expansion to the European Atlantic (Portugal, Galicia, the SW England), and the Macaronesia [56,[58][59][60][61][62][63], while Steen et al [55] reported it from Australia and New Zealand. Steen et al [55] obtained molecular sequence information from historical herbarium samples of Dictyota spp.…”
Section: Case Studies From the Mediterranean Seamentioning
confidence: 99%
“…C. okamurae is native to the NW Pacific, including Japan, Korea, China, and Taiwan, and has recently been reported in many regions, including France (Zuccarello et al, 2002;Burel et al, 2019), Washington (Zuccarello et al, 2002), California (Miller, 2012;Hartnell College Genomics Group et al, 2020), Gulf of California (Norris et al, 2017), Italy (Petrocelli et al, 2020), and Spain (Baŕbara et al, 2019). Recently, after molecular examinations, the name of C. ustulatus has been changed to C. okamurae in several region (Zuccarello et al, 2002;Petrocelli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%